The Phonetic Representation of Spoken Language in Modern Hebrew Literature - Ben‑Shahar, Rina (TTR, 1995)
AbstractThe Phonetic Representation of Spoken Language in Modern Hebrew Literature – Written language normatively transmits the full graphic pattern of a word without deviating from the spelling rules of a particular language. However, when graphic signs are intended to represent the spoken language used in natural conversation, the question of the phonetic imitation of spoken language in written texts arises. The present article deals with the position of spoken language in Hebrew narrative fiction and drama, and the modes of its representation from 1948 on, including both original Hebrew works and those translated from English into Hebrew. This issue is discussed against the background of such relevant broader issues as: the special situation of Hebrew, which had long been used as a written language only, devoid of the varied functions of spoken language; linguistic-stylistic norms in Hebrew literature from 1948 on and the changes they underwent; Hebrew writers' and translators' awareness of the principles of spoken language in general, and those of the Hebrew vernacular in particular; differences in dialogue formation between various literary sub-systems: drama as distinct from narrative fiction and original literature as distinct from translated literature, including some cross-sections of both. The issues are discussed from both the synchronic and diachronic points of view.